(untitled) (The Research of Medical Science Review, 2025)
Urinary tract infections (UTIs) pose a significant burden on healthcare systems worldwide, with a prevalence rate of 20% among patients attending Pakistan Institute of Medical Sciences (PIMS) Islamabad. This study aimed to investigate the distribution and antimicrobial susceptibility patterns of uropathogens causing UTIs among patients visiting PIMS Islamabad. A total of 180 urine samples, collected from patients presenting clinical evidence of UTIs, were analyzed over a two-month period. The majority of patients affected were females (65%) compared to males (35%), with a higher prevalence observed in the age group of 15-25 years. Escherichia coli emerged as the most prevalent uropathogen (33.88%), followed by Candida albicans (30%) and Klebsiella pneumoniae (23.33%). Gram-negative bacteria constituted 62.77% of isolates, with Gram-positive cocci accounting for 7.06%. Antimicrobial susceptibility testing revealed varying resistance patterns among uropathogens, with Penicillin exhibiting the highest resistance (100%) and Vancomycin demonstrating the highest sensitivity (100%). Notably, Amikacin and Nitrofurantoin displayed notable efficacy against E. coli. These findings underscore the importance of targeted antimicrobial therapy in UTI management. The study provides valuable insights into the epidemiology and antimicrobial resistance profile of UTIs in the region, aiding in the development of effective treatment strategies tailored to local conditions. This research contributes to the understanding of UTI dynamics, facilitating improved clinical management and patient outcomes in PIMS Islamabad and beyond.